PENGARUH KARAKTERISTIK KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK ASURANSI PADA PT. SEQUISLIFE INSURANCE CABANG PALEMBANG - Maksum Sofuwan, Tri; Nurrahmi, Maftuhah (Universitas muhammadiyah palembang, 2015)
Formulation of the problem was whether or not there is the influence of Cultural, Social, Personal and Psychology Factors partially and stimultaneously on Purchase decision of Insurance Products at PT. Sequislife Insurance of Branch Palembang. The study aimed for finding out the influence of Cultural, Social, Personal, and Psychology Factors onPurchase Decision of Insurance Products at PT. Sequislife Insurance of Branch Palembang. The study was conducted at PT. Sequislife Insurance of Branch Palembang which adressed Dr. M. Isa Street No.01 Kelurahan 08 IlirKecamatan East Ilir II of Palemban, South Sumatra.The study was conducted by using associate quantitative for finding out the influence among Cultural, Social, Personal, and Psychology Factorson Purchase Decision. The Population was 1000 people. The sample wascollected by using cluster sampling. The data was primary and secondary data. The data was collected by using quesitionare and documentation. The data was analyzed by using quantitative and qualitative. The result showed that cultural and social factors showed negative result, .personal and psychology factors showed positive result, it meanpersonal and psychology factors influenced significantly on purchase decision. Ftest showed there was a significant influence among Cultural (X1), Social (X2), Personal (X3) and Psychology (X4) Factors on Purchase Decision of Insurance Product at PT. Sequislife Insurance of BranchPalembang, Fobtained (58.744) > Ftable (2.4073) with 5%. The independent variable influence on dependen variable stimultaneously